Estimation of genetic gain in milk yield by selection in Sahiwal herds of India - SINGH, S K; NAGARCENKAR, R (The Indian Journal of Animal Sciences, 2013)
The present study was carried out on Sahrwal herds maintaIned at the NDRI, Karnal, and GLF, Ganjaria (Lucknow). The expected genetie changes by direct selection through 4 paths from parent to offspring were calculated. An overall genetic change from direct selection was 23.43 and 3 15 kg per annum which was equivalent to 1.11 Hnd 0.20% of the herd average in Karnal and Ganjana herds respectaly. In Karnal herd, the genetic change from the 4 paths-dam to bull, sire to bull, dam to daughter and sire to daughter respectively 19.98.8.30,0.86 and 0.46% of herd average per generation interval of 8.33, 6.19, 6.11 and 5 26 years respectlvely. The corresponding values in the Ganjaria held wen.: 3.30, 0.51, 0.46 and 0.71 %, of herd ’lvcrage per generation intervai of 8.32, 5.80,6.46 and 4.87 years respectively. Highest genetic change was observed through selection of dams of bulls path in both the herds. This mdicatcd that the bull selection on the basis of their dam’s Performance played cOnsiderable role in brining about favourable genetic changes in milk production in these 2 herds in the absence of systematic and effective progeny testing programmes.